Multiculturalism and social development of Africa and Africans in diaspora in selected arabic literature (2014)
This study intends to investigate multiculturalism as it affects social development of Africa and Africans in Diaspora. It examines the social Problems that hinder the development of Africa as a continent as manifested in selected literary works of four African writers in the field of Arabic literature. The poems of Haflz Ibrahim (1871-1932), a modern poet of Egypt, which addresses social injustice meted out to the African people; Khalll Matran (1872-1948), an Egyptian in diaspora; Ibrahim Najl (1809- 1935). another Egyptian poet, and Abu ‘L-Qasim al-Shabbl (1903-1934), from Tunisia, call for this understudy research. The study identifies social issues that concern Africa and the Africans in diaspora. It explores how multiculturalism would enhance development of Africa and it also proffers Solutions to the identified social obstacles to the development of Africa. It concludes by specifying the multicultural models that would enhance the development of Africa and Africans in diaspora and States that Africa’s development can be maximized with multiculturalism that portrays the uniqueness of the continent and its people in diaspora.